Detection of dengue virus serotype 4 in Panama after 23 years without circulation - Chen-Germán, María; Araúz, Dimelza; Aguilar, Celestino; Vega, Melanie; Gonzalez, Claudia; Gondola, Jessica; Moreno, Lourdes; Cerezo, Lizbeth; Franco, Leticia; Mendez-Rico, Jairo; Pascale, Juan Miguel; López-Vergès, Sandra; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Panama is a country with endemic Dengue virus (DENV) transmission since its reintroduction in 1993. The four serotypes have circulated in the country and the region of the Americas, however, DENV-4 confirmed autochthonous cases have not been identified since 2000, despite its circulation in neighboring countries. Here, we report DENV-4 detection in Panama in the last four-month period of 2023 with co-circulation of the other serotypes, this was associated with a peak of dengue cases during the dry season even though most dengue outbreaks are described in the rainy season. Complete genomes of DENV-4 allowed us to determine that cases were caused by DENV-4 genotype IIb, the same genotype as 23 years ago, with high similarity to DENV-4 sequences circulating in Nicaragua and El Salvador during 2023. This report shows the importance of maintaining serotype and genotype surveillance for early detection of new variants circulating in the country.